REVELATION AND RESEARCH OF UNDERGROUND WATER BASINS AND PALEOVALLEYS: (South-Western part of the Aragats) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
Based on generalization and reinterpretation of long-term data of electroexploration researches carried out in the south-western part of the massif mountain Aragats (Karakert-Aragats area), new maps and profiles of capacities and paleorelief of volcanic (effusive) formations have been compiled. This allowed us to obtain a more refined understanding of the hydrogeological conditions of the studied area. Identified buried groundwater basins and paleochannels are perspective areas for detection of fresh groundwater.
Keywords: Karakert-Aragats area; effusive formations; groundwater basins; paleochannel